Global Economic Prospects, January 2021 - World Bank (Washington, DC: World Bank, 2020)
Although the global economy is emerging from the collapse triggered by COVID-19, the recovery is likely to be subdued, and global GDP is projected to remain well below its pre-pandemic trend for a prolonged period. Several risks cloud the outlook, including those related to the pandemic and to rapidly rising debt. The pandemic has further diminished already-weak growth prospects for the next decade. Decisive policy actions will be critical in raising the likelihood of better growth outcomes while warding off worse ones. Immediate priorities include supporting vulnerable groups and ensuring a prompt and widespread vaccination process to bring the pandemic under control. Although macroeconomic policy support will continue to be important, limited fiscal policy space amid high debt highlights the need for an ambitious reform agenda that bolsters growth prospects. To address many of these challenges, global cooperation will be key.